2019
DOI: 10.1186/s13041-019-0431-x
|View full text |Cite
|
Sign up to set email alerts
|

Motor skills mediated through cerebellothalamic tracts projecting to the central lateral nucleus

Abstract: The cerebellum regulates complex animal behaviors, such as motor control and spatial recognition, through communication with many other brain regions. The major targets of the cerebellar projections are the thalamic regions including the ventroanterior nucleus (VA) and ventrolateral nucleus (VL). Another thalamic target is the central lateral nucleus (CL), which receives the innervations mainly from the dentate nucleus (DN) in the cerebellum. Although previous electrophysiological studies suggest the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
2
27
1
Order By: Relevance
“…indeed, the selective ablation of Dentate-CL neurons has been reported to yield locomotor deficits in the initial performances on the accelerated rotarod (Sakayori et al, 2019), which contrasts with the lack of significant deficit in the Acquisition phase following Dentate-CL (partial) inhibition in our study. A possible explanation could be that our intervention selectively disrupted the advanced patterns of locomotion only needed at the higher speeds of the rotarod.…”
Section: A Specific Impact On Learning Of Dn-cl Neuronscontrasting
confidence: 96%
See 1 more Smart Citation
“…indeed, the selective ablation of Dentate-CL neurons has been reported to yield locomotor deficits in the initial performances on the accelerated rotarod (Sakayori et al, 2019), which contrasts with the lack of significant deficit in the Acquisition phase following Dentate-CL (partial) inhibition in our study. A possible explanation could be that our intervention selectively disrupted the advanced patterns of locomotion only needed at the higher speeds of the rotarod.…”
Section: A Specific Impact On Learning Of Dn-cl Neuronscontrasting
confidence: 96%
“…The inhibition of Interposed-VAL neurons during the task also yield lower levels of performance in the Maintenance stage, suggesting that these neurons contribute also to learning and retrieval of motor skills, although the mild defect in fixed speed rotarod could indicate the presence of an execution problem. Interestingly, both Dentate and Interposed nuclei contain some neurons with collaterals in both thalamic structures (Aumann and Horne, 1996;Sakayori et al, 2019), suggesting that the effect on learning could be mediated in part by a combined action on the learning process of the striatum (via the CL thalamus) and cortex (via the VAL thalamus); however, consistent with (Sakayori et al, 2019), the manipulations of cerebellar neurons retrogradely targeted either from the CL or from the VAL produce different effects.…”
Section: A Specific Impact On Learning Of Dn-cl Neuronsmentioning
confidence: 88%
“…In addition to the cerebellum, multiple brain regions including the cortex and basal ganglia contribute to motor learning on the rotarod ( Sakayori et al, 2019 ). Therefore, we used eyeblink conditioning, an alternate task of motor learning for which the cerebellum is strictly necessary, to validate the motor learning deficits observed in cerebellar KO mice ( Figure 2D ; Heiney et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that a computational modelling study that compared electrode montages targeting M1 and the cerebellum found that cerebellar stimulation produced substantially higher electric field strengths in the target area compared to M1 stimulation, suggesting the cerebellum may indeed be a suitable target for tDCS [38]. Behaviorally, the cerebellum contributes to motor planning, learning, and control; this influence is in part mediated by connections to M1 via the cerebellothalamocortical tracts, previously reported to play a key role in motor skill learning in mice [39]. Although this stimulation technique has received comparatively little attention compared to M1 stimulation, there is some indication that it is possible to modify cerebellar excitability in a focal and polarity specific manner [40].…”
Section: Transcranial Direct Current Stimulation To Improve Lower Limmentioning
confidence: 95%